The research of parameters of multiprobes connecting device for electronic components testing - Невлюдов, И.Ш.; Жарикова, И.В. (Radiotekhnika, 2012)
The problems associated with research into parameters of the multiprobes connecting device for BGA electronic components testing are considered. The results of measurements of the contact resistances and resistances of wires on the flexible connecting board are presented. The received results make it possible to define the needed clamping pressure of a polyamide flexible connecting board to the unit under test and also to be convinced of the uniformity of the testing device designed topology.